2021
DOI: 10.1186/s40543-021-00304-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antidermatophytic activity of bioactive compounds from selected medicinal plants

Abstract: Fungal infections are among the most difficult diseases to manage in humans. Eukaryotic fungal pathogens share many similarities with their host cells, which impairs the development of antifungal compounds. Therefore, it is desirable to harness the pharmaceutical potential of medicinal plants for antifungal drug discovery. In this study, the antifungal activity of sixteen plant extracts was investigated against selected dermatophytic fungi. Of the sixteen plants, the cladode (leaf) of Asparagus racemosus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 91 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The results obtained revealed that, most extracts inhibited fungal growth (MICs) in the range of 0.25 -4.0 μg/ml (Table 4). Savarirajan et al 2021 showed that tannins, flanonoides and saponins respectively were responsible for this antifungal activity. Among these bioactive chemical compounds Fyhrquist et al (2008) highlighted that tannins could be attractive due to their low toxicity to human beings.…”
Section: Resultsmentioning
confidence: 96%
“…The results obtained revealed that, most extracts inhibited fungal growth (MICs) in the range of 0.25 -4.0 μg/ml (Table 4). Savarirajan et al 2021 showed that tannins, flanonoides and saponins respectively were responsible for this antifungal activity. Among these bioactive chemical compounds Fyhrquist et al (2008) highlighted that tannins could be attractive due to their low toxicity to human beings.…”
Section: Resultsmentioning
confidence: 96%